2021
DOI: 10.1111/ecc.13502
|View full text |Cite
|
Sign up to set email alerts
|

Unmet supportive care needs of patients with rare cancer: A systematic review

Abstract: Objective: Patients with rare cancers may experience different unmet needs than those with common cancer. The objective of this systematic review was to (1) investigate unmet supportive care needs of rare cancer patients throughout the disease trajectory and (2) identify predictive factors for these unmet needs.Methods: PubMed, PsycINFO and CINAHL were searched for publications (January 2011 to March 2021) focusing on unmet needs of patients with rare cancer. Two reviewers independently selected studies, extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 102 publications
(174 reference statements)
3
29
0
Order By: Relevance
“…reviewed 23 studies on breast cancer patients and found that the information needs and psychological needs of Asian and Western women differed significantly due to their cultural backgrounds ( 10 ). Another review suggested that patients with rare cancers have unmet needs throughout their disease trajectory, and their supportive care needs should be addressed individually, depending on the rare cancer subdomain and phase of the disease and from diagnosis onwards ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…reviewed 23 studies on breast cancer patients and found that the information needs and psychological needs of Asian and Western women differed significantly due to their cultural backgrounds ( 10 ). Another review suggested that patients with rare cancers have unmet needs throughout their disease trajectory, and their supportive care needs should be addressed individually, depending on the rare cancer subdomain and phase of the disease and from diagnosis onwards ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of supportive care is overlooked in the implementation of novel cancer treatment and demands additional research [ 35 ]. Within the SUBITO study all participating patients should have a consultation with a specialized oncology nurse ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Also, very few cancer patients have mainly reported unmet needs in the post-treatment phase regarding the healthcare system and information, the psychological and the physical, and daily living domain. 44 More than 70% of young adult patients with cancer in Japan reported unmet supportive care needs. Their top unmet needs included psychological needs, physical and daily living needs, health system, information needs, and sexuality needs.…”
Section: Discussionmentioning
confidence: 99%